Analysis of Moral Value in ‘The Silent Child’ Short Movie by Rachel Shenton (2017): Literary Study - Fury Intan Noor Almi; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This research aims to analyze the kinds of moral values and the characteristic of moral values that found in the “The Silent Child” short movie. The method use in this research is qualitative research. Data collection is conducted by watching the short movie of “The Silent Child” and by reading the subtitle. Meanwhile, to analyze the data, the writer conducting some steps. There are; (1). Seeing the movie, (2). Reading the substitle, (3) Identifying moral value found in the movie, (4). Drawing conclusion. The result of this research is we known about a message, moral value such as; bravery, peace ability, confident, wisdom, cooperation, friendliness and kindness, and the dominant moral value in the “The Silent Child” short movie.